1996
DOI: 10.1161/01.str.27.9.1467
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Stroke

Abstract: The identification of depression, social support, and functional status as predictors of quality of life suggests the need to assist stroke survivors in coping and in maintaining and strengthening their support systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
334
3
50

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(432 citation statements)
references
References 23 publications
45
334
3
50
Order By: Relevance
“…Presence of emotional symptoms such as anxiety [30] or Depression adversely affects HRQOL [30,31,32,33,34,35] more than the impairment of physical function [33] because depression negatively influence physical function [34]. Furthermore, stroke leads to substantial deterioration of cognitive function [36] and impaired cognitive function have negative influence on HRQOL [37,38].…”
Section: Psychological Healthmentioning
confidence: 99%
“…Presence of emotional symptoms such as anxiety [30] or Depression adversely affects HRQOL [30,31,32,33,34,35] more than the impairment of physical function [33] because depression negatively influence physical function [34]. Furthermore, stroke leads to substantial deterioration of cognitive function [36] and impaired cognitive function have negative influence on HRQOL [37,38].…”
Section: Psychological Healthmentioning
confidence: 99%
“…Over half of these patients will develop major or minor depression in the acute care rehabilitation settings 142 . In fact, depression is considered to be the strongest predictor of quality of life in this patient population 143,144 and is associated with reduced rehabilitation treatment efficacy, poor functional recovery, poor social outcomes, increased cognitive impairment and increased mortality 145 . Antidepressants, psychostimulants, counseling and psychotherapy are the most commonly prescribed interventions.…”
Section: Mdd In the Rehabilitation Settingmentioning
confidence: 99%
“…A recent study showed that ten to 15 sessions of rTMS applied on the left DLPFC at a frequency of 10Hz, and an intensity of 110% MT was associated with significant reduction of depressive symptoms by 30% and a remission rate of 10% as compared to placebo intervention. Mild and few adverse effects such as headache were reported [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] . Another advantage of the use of rTMS is the improvement in executive functions by rTMS 150,151 .…”
Section: Mdd In the Rehabilitation Settingmentioning
confidence: 99%
“…A depressão nesses pacientes é muito frequente e ela tem sido uma das principais variáveis associadas com a piora da qualidade de vida 30 , dificultando a adesão ao tratamento, comprometendo a percepção geral da saúde, reduzindo os níveis de energia e diminuindo a interação social e a motivação 31 . Vários são os fatores associados ao comprometimento da qualidade de vida, mas a depressão foi considerada um dos mais importantes preditores de baixa qualidade de vida 30,32,33 .…”
Section: Qualidade De Vidaunclassified